Ճալեթի վանքը պատմության քառուղիներում - Ստեփանյան, Գևորգ (Մատենադարան)
According to reliable historical records, since ancient times an Armenian segment coexisted with the Caucasian Albanians in the multi-ethnic region on the left bank of the River Kura. As indigenous and culture-creating nation of the region, the Armenians were actively involved in the socio-political, social-economic, educational and cultural life of the area. On the left bank of the Kura, the Armenian cultural influence is mainly apparent in the spreading and reinforcement of Christianity and literacy. In the late X – early XI centuries, the Armenian eparchies of Shamakhi (Shirvan) and Shak‘i were founded under the jurisdiction of the Catholicosate of Aghvank‘ (called Gandzasar since the end of the 14th century). The residence of the Diocesan Primate of Shak‘i was in the royal domain of the former capital of Aghvank‘ Kapaghak, in the church of the ancient village of Chalet‘, which is very rich in historical monuments. The Surb Astvatsatsin (Holy Theotokos) Monastery in Chalet‘ with its glorious historical past, a unique monument of Armenian architecture, is also one of the centers of medieval Armenian culture. The Monastery was the seat of the Catholicos of Aghvank‘ for more than a century, in the years 1406– 1516. Исторические источники свидетельствуют о том, что к востоку от Армянского нагорья, на разноэтническом пространстве левобережья Куры, с древних времен проживали не только кавказские албанцы (агванцы), но и определенный армянский этнический элемент, который играл особую роль в культурном и политическом развитии края. Автохтоны и культурообразующий народ края, армяне принимали участие в общественно-политической, социально-экономической, культурно-просветительской жизни этого региона. Армянское влияние на этнокультурные процессы левобережья Куры наиболее ярко проявилось в утверждении христианства и распространении письменности. В конце 10-го –начале 11 в. были созданы армянские Шамахийская-Ширванская и Шакийская епархии, находившиеся в подчинении Агванского католикосата (с конца XIV в. стал называться Гандзасарским). Резиденция главы Шакийской епархии находилась в царских владениях бывшей столицы Агванка – престольном Капахаке, в чрезвычайно богатом историческими памятниками армянском селе Чалет, в одноименном монастыре. Имеющий славное прошлое знаменитый монастырь Св. Богородицы в Чалете – своеобразный памятник армянской архитектуры; он был одним из центров армянской средневековой культуры, а с 1406 по 1516 гг. – резиденцией агванских католикосов.
Keywords: Հայ եկեղեցու պատմություն